Plating current density distribution of lithium metal anodes in pouch cells - Yang, Shi-Jie; Shen, Xin; Cheng, Xin-Bing; Jiang, Feng-Ni; Zhang, Rui; Liu, He; Liu, Lei; Yuan, Hong (Journal of energy chemistry, 2022)
The influencing factors of plating current density in lithium metal pouch cells are investigated by experiment and simulation. [Display omitted] The uniformity of current density distribution upon electrodes is one of the most important factors determining the lithium dendrites growth and cycling performance of lithium metal batteries (LMBs). Herein, current density distributions of lithium metal anodes induced by various engineering factors, consisting of uneven cathode, electrolyte distribution, and different tab positions, and their effects on the electrochemical performance are investigated theoretically and experimentally in pouch cells. The deviation of current density in lithium metal anodes ranges from 2.47% to 196.18% due to the different levels of uneven cathode materials. However, the deviation is just 13.60% for different electrolyte thicknesses between cathodes and anodes, even a ten-layer separator in some positions. The maximum deviation for variational tab positions is only 0.17%. The nonuniformity in current density distribution results in severe dendrite growth issues and poor electrochemical performance of LMBs. This work not only confirms the direct correlation between the uneven current density distribution and lithium deposition behaviors, but also points out the decisive effects of cathode surface roughness on current distribution of anodes, to which more attentions should be paid in practical applications of LMBs.